Walking the Talk: LGBTQ Allies in Australian Secondary Schools - Vicars, Mark; Van Toledo, Samara (Frontiers in Sociology, 2021)
Sexual culture(s) are an active presence in the shaping of school relations and LGBTQ issues have long been recognised as being a dangerous form of knowledge in school settings (Epstein & Johnson, 1998). Queer students situated as the sexualised ‘Other’ quickly become the performative object of ‘trouble’, and surveillance surrounding expressions of LGBTQ, has historically, often been aggressively prosecuted and enforced. This paper examines the intersections of straight allies in promoting a LGBTQ visibility and agency in Australian secondary schools. Drawing on interviews with ‘straight’ identified secondary students, a narrative methodology was utilised to explore presence of student allies for making safe schools. Drawing on ‘straight’ secondary students’ responses to LGBTQ issues in their schools, first hand accounts of intervening in heteronorming school cultures focus on experiences being an ally to address LGBTQ inclusivity in Australian secondary schools